AHLI WARISDALAM PERSPEKTIF HUKUM ISLAM DAN KUHPerdata (Burgerlijk Wetbook) - adefariz Ade fahrullah (Hukum Islam, 2021)
AbstractThere are different concepts in determining the people who are entitled to inheritance and their share between Islamic law and the Civil Code. In the concept of Islamic law, heirs are grouped into; dzawil furudh, dzawil ashabah, and dzawil arham. Dzawil furudh and dzawil ashabah are heirs, whose right of acceptance is based on the closeness of blood relations (nasab) with the heir, while dzawil arham is not an heir, who is considered not entitled to receive inheritance as long as there is dzawil furudh and dzawil ashabah. Unlike the case in the Civil Code concept, where heirs are grouped into; class I, class II, class III, and class IV. This group determines the order in which the person is entitled to receive the inheritance. Likewise in terms of the part received by each heir there is a difference in determining the magnitude of the part between the concept of Islamic law and the Civil Code.